Socio-Demographic Influences on Mathematical Word Problem Solving in the Philippine Context: A Narrative Literature Review - Josol, Karl Sebastien; Baloyo, Jovin (JPAIR Institutional Research, 2026)
This narrative literature review examines how socio-demographic factors influence Filipino students' ability to solve mathematical word problems. Drawing on international and local studies, the review synthesizes evidence on the roles of age, sex/gender, and family environment in shaping mathematical literacy. Findings indicate that developmental readiness affects working memory and reading fluency, gender differences are largely influenced by socio-cultural expectations and confidence, and family environment - particularly socio-economic status and parental involvement - is the strongest predictor of performance. By integrating correlational, quasi-experimental, and intervention studies, the review proposes a causal model that situates these factors as key determinants of word problem-solving ability. The study highlights the need for early academic support, gender-sensitive instruction, and strengthened home numeracy practices. These findings provide practical guidance for teachers and policymakers in designing inclusive, evidence-based interventions to improve students' mathematical literacy.
Keywords: mathematical word problems; socio-demographic factors; family environment; Philippine education; mathematics achievement